Night at the museum : battle of the Smithsonian : to the rescue! - Hapka, Cathy; Garant, Robert Ben, 1970-; Lennon, Thomas (New York : HarperCollinsPublishers, 2009)
Larry Daley, who used to be the night guard at the Museum of Natural History in New York City, is aided by Amelia Earhart in his attempts to rescue his friends from the Smithsonian in Washington D.C., and battle against Kahmunrah, the ancient Egyptian ruler.
"2, Reading with help"--Cover p. [4].
"Based on the screenplay by Robert Ben Garant & Thomas Lennon."
Spine title: Night at the museum
1.7
K-3
Keywords: Museums -- Juvenile fiction; Earhart, Amelia, -- 1897-1937 -- Juvenile fiction; Museums -- Fiction; Earhart, Amelia, -- 1897-1937 -- Fiction; Adventure and adventurers -- Fiction; Museums -- Fiction; Earhart, Amelia, -- 1897-1937 -- Fiction; Adventure fiction; Readers (Elementary); Adventure fiction